Boosting the Electrocatalytic Oxygen Evolution of Perovskite LaCo1−xFexO3 by the Construction of Yolk‐Shell Nanostructures and Electronic Modulation. Issue 26 (26th May 2022) - Bao, Bian; Liu, Yana; Sun, Mingzi; Huang, Bolong; Hu, Yang; Da, Pengfei; Ji, Deguang; Xi, Pinxian; Yan, Chun‐Hua
Abstract: Realizing the rational design of perovskite oxides with controllable compositions and nanostructures remains a tremendous challenge for the development of efficient electrocatalysts. Herein, a ligand‐assisted synthetic strategy to fabricate perovskite oxides LaCo1− x Fe x O3 with yolk‐shell nanostructures is developed. Benefiting from the unique structural and compositional merits, LaCo0.75 Fe0.25 O3 exhibits an overpotential of 310 mV at a current density of 10 mA cm −2 and long‐term stability of 100 h for the oxygen evolution reaction. In situ Raman spectroscopy demonstrates that Fe substitution facilitates the pre‐oxidation of Co sites and induces the surface reconstruction into active Co oxyhydroxides at a relatively lower applied potential, guaranteeing excellent catalytic performances. Density functional theory calculations unravel that the appropriate introduction of Fe into perovskite LaCoO3 leads to the improved electroactivity and durability of the catalyst for the oxygen evolution reaction (OER). Fe‐3d orbitals show a pinning effect on Co‐3d orbitals to maintain the stable valence state of Co sites at the low overpotential of the OER. Furthermore, Zn–air batteries (ZABs) assembled with LaCo0.75 Fe0.25 O3 display a high open circuit potential of 1.47 V, superior energy density of 905 Wh kg −1 Zn, and excellent stability in a large temperature range. This work supplies novel insights into the future developments of perovskite‐based electrocatalysts. Abstract : The general ligand‐assisted strategy of constructing yolk‐shell nanostructures is achieved for a series of perovskite oxides LaCo1−x Fex O3 . Structural optimization at the micrometer level and electronic modulation at the atomic level boost the oxygen evolution reaction performance of LaCo0.75 Fe0.25 O3 .